A Mixed Methods Study of the Social Support Networks of Female Sex Workers and Their Primary Noncommercial Male Partners in Tijuana, Mexico. (October 2018) - Wagner, Karla D.; Syvertsen, Jennifer L.; Verdugo, Silvia R.; Molina, Jose Luis; Strathdee, Steffanie A.
Female sex workers (FSWs) are at risk for multiple health harms, including HIV. This article describes a mixed methods study of the social support networks of 19 FSWs and their primary male sex partners in Tijuana, Mexico. We collected quantitative and qualitative social network data, including quantitative network measures, qualitative narratives, and network visualizations. Methodologically, we illustrate how a convergent mixed methods approach to studying personal social support networks of FSWs can yield a more holistic understanding of network composition and role. From a health-related perspective, we show how migration/deportation and stigma shape social networks and might be leveraged to support HIV prevention interventions. We believe others can benefit from a mixed methods approach to studying social networks.